Production and characterization of biodiesel from Camelus dromedarius (Hachi) fat - Mohamed Sbihi, Hassen; Nehdi, Imededdine Arbi; Tan, Chin Ping; Al-Resayes, Saud Ibrahim (Elsevier, 2014)
Recently, biodiesel has been gaining market share against fossil-origin diesel due to its ecological benefits and because it can be directly substituted for traditional diesel oils. However, the high cost of the raw materials required to produce biodiesel make it more expensive than fossil diesel. Therefore, low-priced raw materials, such as waste cooking oil and animal fats, are of interest because they can be used to drive down the cost of biodiesel. We have produced biodiesel from camel fat using a transesterification reaction with methanol in the presence of NaOH. The experimental variables investigated in this study were the temperature (30–75 °C), reaction time (20–160 min), catalyst concentration (0.25–1.5%), and methanol/fat molar ratio (4:1–9:1). A maximum biodiesel yield of 98.6% was obtained. The fuel properties of biodiesel, such as iodine value, saponification value, density, kinematic viscosity, cetane number, flash point, sulfur content, carbon residue, water and sediment, high heating value, refractive index, cloud point, pour point, and distillation characteristics, were measured. The properties were compared with EN 14214 and ASTM 6751 biodiesel standards, and an acceptable level of agreement was obtained.